Algorithmic Management and the Limits of Employer Authority under Indonesian Labor Law - Kurdi Kurdi; Raul Gindo Cahayo; Teuku Ahmad Dadek (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The growing integration of artificial intelligence (AI) into corporate managerial functions has transformed the methods used to monitor and evaluate employee performance. However, it has also increased concerns regarding privacy infringements and algorithmic bias, which may result in disciplinary measures or even employment termination. This study aims to examine the limits of employers’ authority in the use of AI-based performance monitoring systems and to analyze the legal protections available to employees subjected to automated performance evaluations. The research employs a normative legal methodology using statutory and conceptual approaches. The findings reveal that the implementation of AI in employment management must adhere to the principles of legality, transparency, purpose limitation, and human oversight. Furthermore, employee protection can be strengthened through effective complaint mechanisms, procedural fairness, and algorithmic accountability. The study concludes that, although an initial legal framework exists, further regulatory development is necessary to ensure comprehensive protection of employees’ privacy rights and human dignity in the context of AI-driven workplace management.